Immunological therapies involving the use of monoclonal antibodies in renal transplant rejection - Oliveira, Francisca Lourenço de; Gonçalves, Kelly Mayne de Oliveira Gonçalves; Berro, Elaine Cristina; Ugrinovich, Leila Aidar; Simioni, Patricia Ucelli (Brazilian Journal of Transplantation, 2021)
The kidney is an extremely important organ, whose main activity is blood filtration, being responsible for the excretion of undesirable substances in the body. Whenever there is a failure or injury in this organ either due to infections and/ or pathologies, loss of functional capacity may occur, requiring hemodialysis. In more severe cases, transplantation is prioritized. The most common type of graft is allogeneic performed between individuals of the same species, and although there is partial compatibility between the recipient and the donor, there are risks and cases of rejection; so the use of immunosuppressants is essential, involving the use of both conventional and biological therapies. Thus, biological therapies are becoming an alternative treatment for several patients, and the use of monoclonal antibodies is promising, with possible reduction in the dose of immunosuppressant, and reduction of severe side effects. On the market, Muromonab, Basiliximab and Alentuzumab are currently used as therapy in kidney transplanted recipients. The significant decrease in rejection in kidney transplant recipients is partly associated with these biological treatments.